Horizons of Understanding: A Review of Ray Fair's Estimating How the Macroeconomy Works - Fernández-Villaverde, Jesús (Journal of Economic Literature, 2008)
Ray Fair's Estimating How the Macroeconomy Works is the latest in a series of books by Fair that build, estimate, and apply his macroeconometric model to study the U.S. economy. In this book, Fair updates the model to incorporate the most recent data and uses it to analyze several important empirical questions, such as whether the U.S. economy moved into a new age of high productivity in the last half of the 1990s and the dynamics of prices, output, and unemployment. This review places his work in the context of the historical evolution of aggregate econometric models, compares it with the current developments in the estimation of dynamic stochastic general equilibrium models, and discusses some salient aspects of Fair's contributions.